Pakistan : Staff Report for the 2005 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2005)
This 2005 Article IV Consultation for Pakistan reports that macroeconomic performance continues to be strong, but inflation and external pressures are evident. High growth, including in agriculture, is estimated to have raised disposable incomes. The authorities' ambitious growth objectives require substantial increases in investment, including from the private sector. Public investment has been increased to ease bottlenecks in transportation, irrigation, and energy. In the short term, macroeconomic policies need to be tightened somewhat to counter inflation and external pressures.